2003
DOI: 10.1046/j.1439-0418.2003.00760.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of host stage and temperature on selected developmental parameters of the solitary endoparasitoid Meteorus gyrator (Thun.) (Hym., Braconidae)

Abstract: The development of the solitary endoparasitoid Meteorus gyrator was compared in the six larval stages of its host, the tomato moth Lacanobia oleracea, and at five constant temperatures. The host instar at the time of parasitism had a marked effect on the larval developmental period of the parasitoid, such that larvae derived from eggs oviposited in first instar hosts took approximately 18 days to egress, whilst those derived from eggs oviposited in sixth instar hosts took <10 days. The weight of cocoons was gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 21 publications
3
18
1
Order By: Relevance
“…The released hemolymph led to a vigorous cellular defense response by the host, so that some giant capsules were observed particularly in L 1 -L 3 hosts. These results are not consistent with findings on the braconid wasps, Macrocentrus cingulum (Lu et al, 2006) and Meteorus gyrator (Bell et al, 2003). The wasps choose early instars because their immune systems are less able to respond to the wasp's egg or lrava.…”
Section: Discussioncontrasting
confidence: 83%
“…The released hemolymph led to a vigorous cellular defense response by the host, so that some giant capsules were observed particularly in L 1 -L 3 hosts. These results are not consistent with findings on the braconid wasps, Macrocentrus cingulum (Lu et al, 2006) and Meteorus gyrator (Bell et al, 2003). The wasps choose early instars because their immune systems are less able to respond to the wasp's egg or lrava.…”
Section: Discussioncontrasting
confidence: 83%
“…In our experiments, parasitoid cocoon weights also were mostly unaffected by treatment of the host with LoGV. However, both in control and in virus-treated hosts, parasitoid cocoon weights were signiÞcantly affected by the age of the host at the time of parasitism; larger hosts produced larger parasitoid cocoons, results consistent with those of Bell et al (2003). In this study, the weight of the adult parasitoids that subsequently emerged from the cocoons was not determined.…”
Section: Discussionsupporting
confidence: 53%
“…When hosts were treated with LoGV on day 0, and subsequently parasitized from 0 to 11 d later, most mortality in host larvae was due to the virus (parasitoids only developed successfully in those hosts that survived LoGV treatment). This result may well have been due to the differences in the time required for the two biocontrol agents to kill the host; LoGV takes Ϸ7 d to kill its host (Matthews et al 2002) whereas M. gyrator takes as long as 14 d (Bell et al 2003). Therefore, in the majority of cases, those host larvae that were treated with LoGV and then parasitized died of viral infection before the parasitoid had had time to develop inside the host.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies into the ovipositional behaviour of M. gyrator are currently ongoing in order to clarify this aspect of the parasitoids behaviour. Bell et al (2003) reported that this parasitoid could parasitize and develop in all larval stages of L. oleracea that it was presented with. However, the potential for this parasitoid to parasitize a range of hosts had not been investigated.…”
Section: Discussionmentioning
confidence: 99%